SINTESIS SURFAKTAN DIETANOLAMIDA (DEA) DARI METIL ESTER OLEIN SAWIT MENGGUNAKAN REAKTOR 25 LITER - Dora Vitra Meizar, Ani Suryani, dan Erliza Hambali (Jurnal Teknologi Industri Pertanian, 2017)
Synthesis of diethanolamide (DEA) surfactant from palm olein methyl esters has the potential to commercialization. This surfactant product can reduce surface water tension from 72 dyne/cm to 33.82-32.06 dyne/cm in laboratory scale and the synthesis process was 50% cheaper than palm kernel fatty acids. So that, it is necessary to review the surfactant DEA production from palm olein methyl esters. The purpose of this research was to get the best synthesis process of DEA surfactant on 25 L/batch reactor. The synthesis process of DEA surfactants was divided into two stages. The first stage was conducted to determine duration and stirring rate of the DEA surfactant synthesis process. Then the best result in this first stage was continued in the second stage of the synthesis. The second stage was conducted by using an installed bulkhead in the reactor and some agitators for the DEA surfactant synthesis process. The lowest value of surface tension was the main parameter that was used for determining the best synthesis of DEA surfactant. Based on the first stage results, it was known that the best synthesis process was 4 hours with 100 rpm stirring rate. In the second stage, it was concluded that the best type of agitator was propeller. The best surface tension of DEA surfactant resulting from this research was 14.28 dyne / cm. The other parameters produced from the synthesis process were yield of 95.24%, viscosity of 245.41 cP, density of 0.973 g/mL, and pH of 11.1.Key words : DEA surfactant, diethanolamide, surface tension, synthesis process